CODONOBOEA (GESNERIACEAE) SECTIONS IN PENINSULAR MALAYSIA - Chung Lu Lim; Ruth Kiew (Research Center for Biology, 2014)
Codonoboea is the largest genus of Gesneriaceae in Peninsular Malaysia with 92 species. Nine sections, Boeopsis, Codonoboea, Didymanthus, Glossadenia, Heteroboea, Pectinati, Reptantes, Salicini and Venusti, have been erected based on morphological characters, such as habit, leaf arrangement and shape, type of inflorescence, number of flowers, corolla type and nectary type. Recent molecular phylogenetic study using ITS and trnL-F sequences show that only section Heteroboea is monophyletic. While the sections of Codonoboea can no longer be maintained as formal taxonomic taxa, as informal groupings they are useful in identification and in constructing keys.